An accurate filter loading correction is essential for assessing personal exposure to black carbon using an Aethalometer - Good, Nicholas (J Expo Sci Environ Epidemiol, 2016)
The AE51 micro-Aethalometer (microAeth(®)) is a popular and useful tool for assessing personal exposure to particulate black carbon (BC). However, few users of the AE51 are aware that its measurements are biased low (by up to 70%) due to the accumulation of BC on the filter substrate over time; previous studies of personal black carbon exposure are likely to have suffered from this bias. Although methods to correct for bias in micro-Aethalometer measurements of particulate black carbon have been proposed, these methods have not been verified in the context of personal exposure assessment. Here, five Aethalometer(®) loading correction equations based on published methods were evaluated. Laboratory generated aerosols of varying black carbon content (ammonium sulfate, Aquadag(®) and NIST diesel particulate matter) were used to assess the performance of these methods. Filters from a personal exposure assessment study were also analyzed to determine how the correction methods performed for real-world samples. Standard corrections equations produced correction factors with root mean square errors of 0.10 to 0.13 and mean bias within ± 0.10. An optimized correction equation is also presented, along with sampling recommendations for minimizing bias when assessing personal exposure to BC using the AE51 micro-Aethalometer.